Consumer Losses Due to Business Actors in Online Stores: Legal Analysis and Solutions - Susilowati, Asih; Dermawan, I Made; Suwarno, Ernawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
In healthy business or economic activities, a balance of legal protection is needed for consumers and business actors, this is because many consumers are harmed by the fraudulent actions of business actors. The problem formulation is: How is the validity of online transactions via Instagram viewed from Article 1320 of the Civil Code and what form of legal protection is provided for consumers due to losses by online shop business actors on Instagram. Normative juridical research method with a qualitative approach. The legal basis for online transactions is the same as transactions in general, referring to the basic provisions of Article 1320 of the Civil Code as a condition for the validity of the agreement, whereas online sales and purchase agreements remain as valid as conventional sales and purchase agreements, if they still comply with Article 1320 of the Civil Code. If the consumer's rights are not fulfilled, the consumer can take legal action as regulated in Article 38 and Article 39 paragraph (2) of the ITE Law and Article 47 and Article 48 of the Consumer Protection Law. Suggestions that can be given in the future need to be made legal regulations that specifically regulate e-commerce so that consumer rights in electronic transactions, especially using Instagram media, which is not used for selling purposes like other e-commerce which is specifically designed for online shopping, can be better guaranteed.